Challenges in Teaching English Speaking and Listening Skills in Rural Nepal (Voice: A Biannual & Bilingual Journal, 2024)
This study investigates the challenges faced by secondary level English teachers in teaching speaking and listening skills in rural areas of Nepal. The research was carried out in Geruwa Rural Municipality, Bardiya District. A phenomenological research design was used and data was collected through semi-structured interviews with 11 English teachers. The findings revealed six main challenges: inadequate lesson planning, low teacher language proficiency, limited awareness of the curriculum, lack of resources and infrastructure, limited professional development opportunities and lack of collaborative support. Teachers reported struggling with time management due to administrative tasks which affected their ability to plan effective lessons. Many teachers lacked confidence in their English speaking skills. This impacted their teaching. Moreover, inadequate teaching resources and poor infrastructure hindered effective learning. The study suggests the need for more resources, better curriculum training and professional development programs to support teachers. This research highlights the systemic issues that affect English teaching in rural areas.